Violent Deaths and Traumatic Bereavement: The Importance of Appropriate Death Notification - Diego de Leo; Cristina Anile; Anna Ziliotto (Humanities, 2015)
The communication of a death due to unexpected and traumatic causes is considered a very sensitive issue that can deeply affect both operators responsible for reporting the incident and the mourning process of family members, relatives, and other survivors. By focusing particularly on cases of traumatic death, this article tries to explain how inadequate communication of death may adversely affect the course of mourning. The article also illustrates the basic principles of correct notification of death. In this way, we hope to contribute to the ongoing dialogue on this topic and the promotion of new studies aimed at setting best practices for those professionally involved in the challenging task of communicating that a life has ended. This would be important in order to safeguard the emotional integrity of notifiers whilst effectively helping the survivors to cope with the early stages of their difficult mourning process.